The Mouth‐Gut‐Brain model: An interdisciplinary approach to facilitate reformulation of reduced fat products. Issue 3 (22nd August 2019) - Yeomans, M. R.; Zhou, X.; Wilde, P.; Thomas, A.; Linter, B.; Beri, A.; Lovegrove, J. A.; Williams, C. M.; Methven, L.
Abstract: The food industry faces the difficult challenge of reformulating many of their products to meet increasingly stringent targets to reduce energy density by adjusting fat and sugar levels. However, reducing fat in products raises multiple risks for consumer satisfaction because of the consequent effects on both the multimodal sensory experience of the product and the extent to which satiety post‐ingestion meets expected satiety. Recognising that this complex problem requires an interdisciplinary approach, the Mouth‐Gut‐Brain project brought together academic expertise in food and sensory science, the psychology of appetite and the biophysics of food microstructure, with the support of seven industry partners, to develop novel, innovative approaches to enable successful reformulation of fat in a snack context. The project recognised the multifaceted nature of fat perception, and how it affects the psychological and physiological responses to consumption and ingestion. The outcomes of the research programme, comprising the characterisation of sensory and satiety responses of volunteers in the context of two novel fat‐reduced snack products, will be published over the next year and will help inform future novel approaches to fat reduction.